The effect of SiO₂ microparticle concentration on the electrical and thermal properties of silicone rubber for electrical insulation applications - Ahmed, Zahraa; Nasrat, Loai S.; Rihan, Mahmoud (Національний технічний університет "Харківський політехнічний інститут", 2025)
Polymeric insulators, first developed in the 1950s, have since seen substantial advancements in both design and manufacturing, making them increasingly appealing to users and manufacturers in the electrical industry. Extensive testing in both laboratory and outdoor environments has consistently demonstrated that polymeric insulators outperform traditional porcelain and glass counterparts. Among the various polymeric materials, silicone rubber (SiR) has emerged as one of the most promising candidates for highvoltage insulators. Its superiority is attributed to a unique combination of properties, including a non-conductive chemical structure, high dielectric strength, and excellent resistance to scaling. To further enhance these properties, SiR is often combined with fillers to form composite materials. These SiR composites are at the forefront of advanced high-voltage insulation systems, offering improved mechanical, thermal, and electrical performance. As a result, they not only meet the rigorous demands of high-voltage applications but also provide a significantly extended service life. Goal. This study aims to enhance the dielectric and thermal properties of SiR by incorporating micron-sized silicon dioxide (SiO2) filler. Methodology. SiR-based composite samples were prepared by incorporating micron-sized SiO2 at weight fractions of 10 %, 20 %, 30 %, and 40 % of the total composition. Initially, the samples were heated to specific temperatures (25°C, 60°C, 80°C, and 100°C) before undergoing dielectric strength testing to evaluate their performance under varying thermal conditions. Additionally, the samples were subjected to thermal aging for durations of 10, 20, and 30 minutes at the same temperatures before dielectric strength assessment. The results indicated that increasing the filler concentration enhanced the dielectric strength of the SiR/SiO2 composites. The highest breakdown voltage was observed at a filler concentration of 30 %. Practical value. Incorporating micron-sized SiO2 filler into the SiR matrix enhanced the composite's resistance to thermal stress. Compared to SiR-based composites with varying SiO2 concentrations, pure SiR exhibited the lowest dielectric strength.

Полімерні ізолятори з моменту розробки в 1950-х роках значно удосконалилися як у проєктуванні, так і у виробництві, що робить їх все більш привабливими для користувачів та виробників електротехнічної продукції. Великі випробування як у лабораторних, так і промислових умовах демонструють, що полімерні ізолятори переважають традиційні порцелянові і скляні аналоги. Серед різних полімерних матеріалів силіконовий каучук (SiR) став найперспективнішим матеріалом для високовольтних ізоляторів. Його перевага пояснюється унікальним поєднанням властивостей, включаючи непровідну хімічну структуру, високу діелектричну міцність та відмінну стійкість до утворення накипу. Для подальшого покращення цих властивостей, SiR часто поєднують з наповнювачами для формування композитних матеріалів. Ці композити SiR знаходяться на передньому країсучасних систем високовольтної ізоляції, пропонуючи покращені механічні, теплові та електричні характеристики. В результаті вони не тільки відповідають жорстким вимогам високовольтних застосувань, а й забезпечують значно більший термін служби. Метою дослідження є покращення діелектричних та теплових властивостей SiR шляхом включення наповнювача діоксиду кремнію (SiO2) мікронного розміру. Методологія. Зразки композиту SiR були приготовлені шляхом включення різних вагових відсотків мікронного розміру SiO2 відповідно 10 %, 20 %, 30 % та 40 % від загальної ваги. Потім діелектрична міцність цих зразків була оцінена за чотирьох температур: 25 °C, 60 °C, 80 °C і 100 °C для оцінки ефективності ефекти в різних умовах. Крім того, зразки старіли протягом 10, 20 і 30 хвилин при тих же температурах перед випробуванням. Результати досліджували вплив термічноїповедінки на характеристики напруги пробою композитів SiR, зістарених у різний час і за різних температур. Результати показують, що збільшення концентрації наповнювача збільшує діелектричну міцність SiR композитів. Найкраща пробивна напруга досліджених зразків була отримана при концентраціїнаповнювача 30 %. Практична цінність. Додавання наповнювача SiO2 мікронного розміру в матрицю SiR підвищує опір полімерних композитів термічним механічним напругам. У порівнянні з SiR, завантаженим SiO2 у різних концентраціях, чистий SiR має найнижчу діелектричну міцність.
Keywords: dielectric strength; silicone rubber; micron-sized silica dioxide; thermal behavior; neural network; діелектрична міцність; силіконова гума; діоксид кремнію мікророзміру; термічна поведінка; нейронна мережа